The Outcome of Surgical and Radiotherapy in Central Neurocytoma: A Case Report: The Outcome of Surgical and Radiotherapy in Central Neurocytoma: A Case Report - Ardhini, Rahmi; Tsaniadi Prihastomo, Krisna; Firli Bramantyo, Dion; Tugasworo, Dodik; Retnaningsih, Retnaningsih; Andhitara, Yovita Andhitara; Kurnianto, Aditya Kurnianto; Budiman, Jethro (Medica Hospitalia : Journal of Clinical Medicine, 2022)
BACKGROUND: Central neurocytoma (CN) is an infrequent and non-malignant neuro-epithelial tumor. CN is mostly found in lateral ventricle and may generate obstructive hydrocephalus. Surgical-radiation can increase patient survival and prognosis. This case report presented a rare case about 30-year-old female with CN. CASE PRESENTATION: 30-year-old female came to the hospital with severe headache and vomiting. Brain MRI showed a heterogeneous mass in right lateral ventricle causing obstructive hydrocephalus. The patient undergone partial resection. CN confirmed from histopathological analysis. Afterward, patient received 54 Gy conventional radiotherapy. 3 months after radiation, patient remain asymptomatic and no neurological deficit. Brain MRI evaluation showed slightly reduction of tumor mass (from 4,09 x 3,01 x 4,13 cm before radiation to 4,00 x 3,86 x 3,63 cm after radiation). DISCUSSION: This case report was consistent clinically, radiologically, and histopathologically with intraventricular CN. Headache and vomiting in patient due to the raised intracranial pressure from tumor mass and obstructive hydrocephalus. Headache is a significant and most frequent symptom in intraventricular tumors, may be caused by traction or compression of the pain-sensitive structures such as meningen and intracranial vasculature. Optimal management of CN still remains controversial due to their rarity. However, surgical management with gross total resection is the gold standard of treatment modality, associated with good prognosis and longer progression-free survival. CONCLUSION: Based on clinical characteristic, radiographic finding and histopathological features; this case was consistent with CN of the lateral ventricle. Surgical as the treatment option followed by radiation has led to good clinical outcome in this patient. KEYWORDS: central neurocytoma, hydrocephalus, neuro-epethelial tumor, radiotherapy